PROSES PENGECORAN ADAPTOR PADA BUCKET TEETH UNTUK EXCAVATOR DENGAN MENGGUNAKAN METODE PEMBUATAN CETAKAN FURAN - Ariyanto Ariyanto (Asosiasi Dosen Muda Indonesia, 2023)
The following paper was made to understand the process, and defects from metal casting of Low Carbon Steel GS-25 CrMo 4 Bucket Teeth Adaptor for Excavator with furan molding method and how the results of the Chill Test on the product. Metal casting process of making objects by melting metal and pouring it into a mold cavity. Metal casting has been discovered and continues to be developed, one of which is Sand Casting, where there are various types of methods in making molds including the Furan, Disamatic, and Jolt Squeeze methods. The method used in this research is the Furan method which can be used to make objects with complex shapes such as the Adaptor component used in the Bucket Teeth for Excavators. The casting material used in this casting is GS-25 CrMo 4 steel which has strong and tough properties. All manufacturing processes are carried out through several stages, namely; design, model and core making, mold making, smelting, pouring, fettling and finishing, and quality control. From the results of the research that has been carried out, it can be seen that several rejections from these products include: cold shut, missrun, inoculant inclusion, slag inclusion, and sand inclusion.